Promoting physical activity: development and testing of self-determination theory-based interventions - Fortier Michelle S; Duda Joan L; Guerin Eva; Teixeira Pedro J (BMC, 2012)
Abstract A growing number of studies have pulled from Deci and Ryan's Self-Determination Theory to design interventions targeting health behavior change. More recently, researchers have begun using SDT to promote the adoption and maintenance of an active lifestyle. In this review, we aim to highlight how researchers and practitioners can draw from the SDT framework to develop, implement, and evaluate intervention efforts centered on increasing physical activity levels in different contexts and different populations. In the present paper, the rationale for using SDT to foster physical activity engagement is briefly reviewed before particular attention is given to three recent randomized controlled trials, the Canadian Physical Activity Counseling (PAC) Trial, the Empower trial from the UK, and the Portuguese PESO (Promotion of Health and Exercise in Obesity) trial, each of which focused on promoting physical activity behavior. The SDT-based intervention components, procedures, and participants are highlighted, and the key findings that have emanated from these three trials are presented. Lastly, we outline some of the limitations of the work conducted to date in this area and we acknowledge the challenges that arise when attempting to design, deliver, and test SDT-grounded interventions in the context of physical activity promotion.